Multidrug-resistant Streptococcus pneumoniae causing invasive pneumococcal disease isolated from a paediatric patient. (January 2020) - Arushothy, Revathy; Ramasamy, Hema; Hashim, Rohaidah; Raj A.S, Santhana; Amran, Fairuz; Samsuddin, Nazirah; Ahmad, Norazah
Highlights: The emergence of non-vaccine pneumococcal serotypes is an increasing concern in Malaysia. Non-vaccine serotypes show the possibility of horizontal gene transfer from serotype 19A or 23F. Continuous pneumococcal surveillance of serotypes and antimicrobial resistance is crucial for patient management. Abstract: The emergence of non-vaccine multidrug-resistant Streptococcus pneumoniae serotypes is on rise. This study was performed to investigate a highly resistant serotype 15A S. pneumoniae isolated from the blood specimen of a 20-month-old patient who died of her infection. The SS40_16 isolate was resistant to erythromycin, co-trimoxazole, tetracycline, and chloramphenicol, as well as to penicillin, ceftriaxone, and cefotaxime (using meningitis cut-off points, Clinical and Laboratory Standards Institute). The isolate belonged to sequence type 1591 (ST1591) and was related to CC81 clonal complex, suggesting the possibility of horizontal gene transfer. Scanning electron microscopy comparison between resistant and sensitive pneumococcal isolates also indicated similar phenotypic characteristics that confer high resistance. The emergence of highly resistant non-vaccine pneumococci is of great concern to public health and in the clinical setting. Pneumococcal surveillance programs represent a crucial tool, not only for determining the impact of pneumococcal conjugate vaccines, but also for monitoring the selective pressure of serotype replacement with regard to the treatment of invasive pneumococcal disease.